Penile Anatomy and Hypotheses of Erectile Function in the American Alligator (Alligator mississippiensis): Muscular Eversion and Elastic Retraction. Issue 3 (13th February 2013) - Kelly, D.A.
<x xml:space="preserve">Abstract</x> The intromittent organs of most amniotes contain variable‐volume hydrostatic skeletons that are stored in a flexible state and inflate with fluid before or during copulation. However, the penis in male crocodilians is notable because its shaft does not seem to change either its shape or bending stiffness as blood enters its vascular spaces before copulation. Here I report that crocodilians may have evolved a mechanism for penile shaft erection that does not require inflation and detumescence. Dissections of the cloaca in sexually mature male American alligators (Alligator mississippiensis) show that the cross section of the proximal shaft of the alligator penis contains dense collagenous tissues that do not significantly change shape when fluid is added to the central vascular space. The large amount of collagen in the wall and central space of the alligator penis stiffen the structure so it can be simply everted for copulation and rapidly retracted at its completion. Because no muscles insert directly onto the penis, eversion and retraction must be produced indirectly. My results suggest that the contraction of paired levator cloacae muscles around the anterior end of the cloaca rotates the penis out of the cloacal opening and strains the ligamentum rami that connect the base of the penis to the ischia. When the cloacal muscles relax, the elastic recoil of the ligamentum rami can return the penis to its original position inside the cloaca. Anat Rec, 296:488–494, 2013. © 2013 Wiley Periodicals, Inc.